2004
DOI: 10.1097/01.iop.0000116380.53725.d3
|View full text |Cite
|
Sign up to set email alerts
|

Eyelid Merkel Cell Carcinoma: Report of Three Cases

Abstract: The rarity of eyelid Merkel cell carcinoma and the fact that it can simulate benign entities frequently lead to difficulties in diagnosis and a delay in the establishment of suitable therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…166,172 Unusual presentations, including a multinodular conjunctival mass and a tumor with tarsal invasion, have been reported. 172,173,[176][177][178] Immunohistochemistry is often needed to diagnose MCC, which exhibits a characteristic perinuclear dot pattern with CK-20 and stains positive for neuron-specific enolase, chromogranin, and others. 172,173,[176][177][178] Immunohistochemistry is often needed to diagnose MCC, which exhibits a characteristic perinuclear dot pattern with CK-20 and stains positive for neuron-specific enolase, chromogranin, and others.…”
Section: Cutaneous Melanomamentioning
confidence: 99%
See 1 more Smart Citation
“…166,172 Unusual presentations, including a multinodular conjunctival mass and a tumor with tarsal invasion, have been reported. 172,173,[176][177][178] Immunohistochemistry is often needed to diagnose MCC, which exhibits a characteristic perinuclear dot pattern with CK-20 and stains positive for neuron-specific enolase, chromogranin, and others. 172,173,[176][177][178] Immunohistochemistry is often needed to diagnose MCC, which exhibits a characteristic perinuclear dot pattern with CK-20 and stains positive for neuron-specific enolase, chromogranin, and others.…”
Section: Cutaneous Melanomamentioning
confidence: 99%
“…[173][174][175] The diagnosis of MCC is uncommon, so this malignancy tends to be misdiagnosed initially, with the differential diagnosis including chalazion, BCC, cyst, nodular angiosarcoma, and metastasis; with the correct diagnosis being made only after biopsy. 172,173,[176][177][178] Immunohistochemistry is often needed to diagnose MCC, which exhibits a characteristic perinuclear dot pattern with CK-20 and stains positive for neuron-specific enolase, chromogranin, and others. 172,173,176 Metastatic small-cell lung cancer can mimic MCC histologically but stains with thyroid transcription factor-1, whereas MCC does not.…”
Section: Cutaneous Melanomamentioning
confidence: 99%
“…5 At present, the role of SLNB in this disease remains unclear: it may have a role in selected patients detecting nodal involvement as an alternative to elective regional lymph node dissection that is associated with significant morbidity and no impact on survival. 5,12,15,18 Multiple studies have shown that adjuvant chemotherapy in the management of MCC has short-lived benefit, does not improve survival, 19 and has significant mortality associated with its use. 20 The role of chemotherapeutic agents is limited to metastatic disease or palliation of inoperable regional disease.…”
Section: Discussionmentioning
confidence: 99%
“…They tend to follow a predictable pattern of spread to the regional lymph nodes and then systemic metastasis. 5 Sentinel lymph node assessment assists in the staging of this tumour. 6 Kivela and Tarkkanen 2 reported that one third of these tumours recur, almost two thirds give rise to regional node metastases, and up to a half metastasize systemically and result in death.…”
Section: Commentsmentioning
confidence: 99%
“…The clinical and histopathologic differential diagnoses should also include lymphoma, leukemic infiltrate, metastatic small cell carcinoma of the lung, and amelanotic melanoma. 5 Although MCC has characteristic clinical features, the diagnosis generally relies on histopathologic identification. 1 Immunohistochemistry is required to differentiate MCC from other small round cell tumours; however, clinical correlation may be required in differentiating MCC from other neuroendocrine tumours that have metastasized to the eyelids.…”
Section: Commentsmentioning
confidence: 99%